Mandatory bulk billing policies may have differential rural effects: an exploration of Australian data - Belinda O'Sullivan; Rebecca Kippen; Helen Hickson; Glen Wallace (James Cook University, 2022)
Introduction: Over the course of the COVID-19 pandemic, Australian general practices have rapidly pivoted to telephone and video call consultations for infection control and prevention. Initially these telehealth consultations were required to be bulk billed (doctors could only charge fees equivalent to the national Medicare Benefits Schedule (MBS)). The potential impact of this policy on general practices − and particularly rural general practices - has been difficult to assess because there is limited published data about which practices are less likely to bulk bill and therefore more impacted by mandatory bulk billing policies. There was concern that bulk billing only policies could have a broader impact on rural practices, which may rely on mixed or private billing for viability in small communities where complex care is often needed. This study aimed to understand the patterns of bulk billing nationally and explore the characteristics of practices more or less likely to bulk bill patients, to identify the potential impact of a rapid shift to bulk billing only policies. Methods: General practice bulk billing patterns were described using aggregate statistics from Australian Department of Health public MBS datasets. Bulk billing rates were explored over time by rurality, and state or territory. Next, questions about bulk billing were included in a cross-sectional survey of practices conducted in 2019 by General Practice Supervisors Australia (GPSA). Practice bulk billing patterns were explored by rurality, state or territory and practice size at univariate level before a multivariate logistic regression model was done, including the statistically significant variables. Results: Nationally, bulk billing rates for general practice non-referred attendances increased over 2012-2019 from 82% to 86% but declined slightly in Modified Monash Model (MMM)2−7 (rural areas) at the end of this period. Further, bulk billing rates varied by rurality, and were highest in very remote (MMM7) (89-91%) and metropolitan areas (MMM1) (83-87%) and lowest in regional centres (MMM2) (76-82%) over this period. The results from the GPSA survey concurred with national data, showing that the proportion of practices bulk billing all patients was highest in metropolitan locations (28%) and lowest in regional centres and large rural towns (MMM2−3) (16%). Smaller practices (five or fewer general practitioners) were more likely to bulk bill all patients than were larger ones (six or more general practitioners). Multivariate modelling showed that bulk billing all patients was statistically significantly (p<0.05) less likely for larger practices compared with smaller ones, and for rural practices (MMM2−7) compared with those in metropolitan areas. Conclusion: Mandatory bulk billing policies should accommodate the fact that bulk billing varies by context, including rurality and the size of a practice, and has been decreasing in rural areas over recent years. Rapidly pivoting to bulk billing only service models may put pressure on rural and large practices unless they have time to adjust their business models and have ways to offset the loss of billings. Policies that allow for a range of billing arrangements may be important for practices to fit billings to their local context of care, including in rural settings, thereby supporting business viability and the availability of sustainable primary care services.